2015
DOI: 10.1007/s00520-015-2904-5
|View full text |Cite|
|
Sign up to set email alerts
|

Safety of long-term denosumab therapy: results from the open label extension phase of two phase 3 studies in patients with metastatic breast and prostate cancer

Abstract: PurposeZoledronic acid (ZA) or denosumab treatment reduces skeletal-related events; however, the safety of prolonged therapy has not been adequately studied. Here, we describe safety results of extended denosumab therapy in patients with bone metastases from the open-label extension phase of two phase 3 trials.MethodsPatients with metastatic breast or prostate cancer received subcutaneous denosumab 120 mg Q4W or intravenous ZA 4 mg Q4W in a double-blinded fashion. Denosumab demonstrated superior efficacy in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
150
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(159 citation statements)
references
References 28 publications
6
150
0
3
Order By: Relevance
“…In their recent article, Stopeck et al [1] concluded that denosumab confirms its known safety profile even after longterm exposure, or after switching to it from zoledronic acid, and that osteonecrosis of jaws (ONJ) rates increased with increasing exposure to antiresorptives, consistent with previous reports. This is based on the open label extension phase of two phase 3 studies in patients with breast and prostate cancer with bone metastases who were randomized to receive denosumab or zoledronic acid (ZA) [2,3].…”
Section: To the Editorsupporting
confidence: 66%
See 3 more Smart Citations
“…In their recent article, Stopeck et al [1] concluded that denosumab confirms its known safety profile even after longterm exposure, or after switching to it from zoledronic acid, and that osteonecrosis of jaws (ONJ) rates increased with increasing exposure to antiresorptives, consistent with previous reports. This is based on the open label extension phase of two phase 3 studies in patients with breast and prostate cancer with bone metastases who were randomized to receive denosumab or zoledronic acid (ZA) [2,3].…”
Section: To the Editorsupporting
confidence: 66%
“…We collected data from the text and the tables of the paper published by Stopeck et al [1] and summarized them in a new table (Table 1).…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…In any case, the safety profile of DMab after long-term exposure is 19.1 months in breast cancer and 12 months in prostate cancer. 13 Finally, metastatic kidney cancer is a special case. This patient setting is particularly susceptible to ONJ due to the concomitant use of antiangiogenic drugs that block vascular endothelial growth factor (VEGF).…”
Section: Stagementioning
confidence: 99%